Differences in behavioral health disorders and unmet treatment needs between medical marijuana users and recreational marijuana users: Results from a national adult sample. (1st November 2017) - Park, Ji-Yeun; Wu, Li-Tzy
Highlights: Three marijuana groups (recreational only, medical only, and both) were examined. Behavior health disorders and unmet treatment need were common in both-use group. Sex-specific associations with behavioral health differed between marijuana groups. Behavioral health assessment should consider motives for marijuana use. Results suggest the need for sex-specific behavioral health intervention. Abstract: Background: Available data suggest that medical marijuana users may have more mental health problems than recreational marijuana users. There is limited information about differences in behavioral health disorders and unmet treatment needs between medical and recreational marijuana users. Methods: We compared past-year prevalence of behavioral health disorders and unmet treatment needs across three marijuana subgroups (recreational use only, medical use only, and both). Sex-stratified logistic regression was performed to determine their associations with marijuana use status. We analyzed data from adults (≥18 years) who used marijuana in the past year (N = 15, 440) from 2013 to 2014 National Surveys on Drug Use and Health. Results: Among 15, 440 past-year marijuana users, 90.2% used recreational marijuana only, 6.2% used medical marijuana only, and 3.6% used both. Both users had the highest prevalence of behavioral health disorders and unmet treatment needs overall, with no significant sex differences. In the sex-specific logistic regression analysis, medical only users and both users showed somewhat different patterns of associations (reference group = recreational only users). Medical only users had decreased odds of alcohol or drug use disorders, and unmet need for alcohol or drug treatment among males and females. Additionally, female medical only users had decreased odds of opioid use disorder. Both users had increased odds of major depressive episode, hallucinogen use disorder, and unmet need for mental health services among males, and cocaine use disorder among females. Conclusions: Different approaches tailored to individuals' sex and motives for marijuana use is needed for the prevention and treatment of behavioral health problems.